Dari Hafalan ke Mushaf: Kritik Historis dan Otoritas Mushaf Utsmani - Qarinah, Qarinah; Abubakar, Achmad; Chalik, Sitti Aisyah (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2026)
This study aims to trace the process of the Qur’anic codification from the time of Prophet Muhammad (peace be upon him) to the caliphate of ʿUthmān ibn ʿAffān, as well as to analyze the formation and authority of the rasm ʿUthmānī as the standardized model of Qur’anic writing in the Islamic world, particularly in Indonesia. The research employs a descriptive-historical and theological-analytical method, highlighting the continuity of the codification process from the Prophet’s era to that of ʿUthmān and the legitimacy of the rasm ʿUthmānī authenticity based on the ijmāʿ (consensus) of the Companions. The findings indicate that the codification of the ʿUthmānic mushaf represents a continuation of the Prophet’s efforts to preserve divine revelation and serves as an essential instrument in maintaining the textual authenticity and unity of the Muslim community across time, from the classical to the modern period. The implications of this study emphasize the importance of strengthening Muslim awareness of the historical and theological significance of the rasm ʿUthmānī as a symbol of unity and the authenticity of divine revelation, while also opening avenues for further research on the authority of the mushaf and the application of the rasm ʿUthmānī in the digital era.